2018
DOI: 10.1002/sono.12146
|View full text |Cite
|
Sign up to set email alerts
|

The role of deliberate practice in development of essential sonography skills

Abstract: The role of deliberate practice (DP) theory in the development of expert performance has been widely studied. This paper reviews the concept of DP and the various factors that could impact the development or refining of essential sonography skills for students and practitioners. In this article, the authors review the concept of DP for its potential benefits and limitations in Medical Sonography education and its potential impact on the future calibre of practitioners. The paper encourages both novice and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…CPD is further training completed after formal education to maintain a high level of knowledge and skills, while developing the personal and professional qualities required throughout a sonographer's professional life . The benefits of in‐person CPD activities is well‐researched, as it allows the health care professional to effectively improve a specific shortcoming within their practical skillset through hands‐on instruction taught by an expert in the field …”
Section: Introductionmentioning
confidence: 99%
“…CPD is further training completed after formal education to maintain a high level of knowledge and skills, while developing the personal and professional qualities required throughout a sonographer's professional life . The benefits of in‐person CPD activities is well‐researched, as it allows the health care professional to effectively improve a specific shortcoming within their practical skillset through hands‐on instruction taught by an expert in the field …”
Section: Introductionmentioning
confidence: 99%
“…25 Importantly, it has been widely acknowledged that the person scanning is responsible for documenting any abnormalities with appropriate image selection, ultimately instigating the diagnosis. 25,26 An essential rapport is established between the patient and the sonographer during a sonographic examination. Despite this, in Australia there is a lack of uniformity in policy, practice, and expectations surrounding communication of adverse findings with the patient, who expects nothing less than full information.…”
Section: Discussionmentioning
confidence: 99%
“…Stage three relates to intentional practice 34 of a skill, and end‐task or terminal feedback 22,40 . Deliberate skill practice is essential to learn psychomotor scanning skills 33,36,37 . The skill practice format used will either advance or hinder the learner's acquisition of the psychomotor skill.…”
Section: Discussionmentioning
confidence: 99%
“…22,40 Deliberate skill practice is essential to learn psychomotor scanning skills. 33,36,37 The skill practice format used will either advance or hinder the learner's acquisition of the psychomotor skill. This study found that up to 64% of the respondents use short sessions of skill practice of less than 60 min duration, while 42% used long sessions of more than 60 min duration.…”
Section: Stage Threementioning
confidence: 99%